Pembaruan Definisi Asuransi dalam Sistem Hukum di Indonesia - Purwanto (Jurnal Risalah Hukum, 2006)
Orientated on either article 1233 of KUHPerdata, so the definition involves in article 246 of KUHD, article 1 point 1 of UU No. 2 Tahun 1992 tentang Usaha Perasuransian, or some experts’ opinion that state insurance is as an agreement can be only connected or used for insurance in which it’s participatory is voluntary. That definition is too narrow, less relevant with the regulation and social insurance program development so that need to make renewal in order to make it suitable either with social insurance program development’s fact or theory of law in jurisprudence. Thus, the insurance definition renewal is expected can be used as the fundamental in learning either law of insurance’s aspect or the execution of insurance work in Indonesia. Key words: asuransi (insurance), program asuransi sosial (social insurance program), perjanjian (agreement), perikatan (verbintenis).